[I093] Mr-guided radiotherapy at the LMU in Munich: Preliminary studies. (August 2018) - Kamp, Florian; Neppl, Sebastian; Rabe, Moritz; Nierer, Lukas; Kurz, Christopher; Reiner, Michael; Belka, Claus
Abstract : Purpose: The clinical introduction of an MR-guided radiotherapy unit offers great potential to improve future patient treatment but is at the same time associated with several challenges from the perspective of medical physics. Before the final implementation of an MR-Linac in our clinical environment several preliminary studies are performed to prepare the introduction of the new system into the routine patient care as well as covering medical physics related research aspects. Methods: One focus of the projects is a comparison of the adaptive workflow based on daily MR and daily cone beam CT imaging. In order to mimic the MR-guided radiotherapy workflow an MR-compatible flat table top is equipped with immobilization devices for offline MR imaging in treatment position. A flexible, modular phantom is developed based on lego bricks, enabling fast distortion phantom prototyping and consequently distortion measurements. The effect of magnetic fields on dose measurements with thermoluminescent dosimeters is evaluated. Image registration methods are applied to time-resolved 4D MR and 4D CT images of patients as well as to breathing phantoms evaluating how to include 4D data into the online adaptive treatment workflow. Results: The preliminary results of the projects mentioned above will be presented and discussed. This includes a comparison of CT- and MR-based internal target volume concepts as a surrogate for reproducibility of breathing motion of the patient, the first results of the 4D phantom studies and the TLD measurements in a magnetic field. Conclusions: Several studies are performed at the university hospital of the LMU in Munich to pave the way for a smooth introduction of the MR-Linac into clinical routine and into research in MR-guided radiotherapy.